Modern Arabic Literature (Al-Farooq Journal of Sciences, 2026)
This research examines Modern Arabic Literature in terms of its concept, emergence, types, factors of development, characteristics, and major literary schools. Modern Arabic literature represents an important stage in the history of Arabic literature, as it marked a transition from the state of stagnation that prevailed during the late Ottoman period to the stage of revival and renewal that began at the beginning of the nineteenth century.The first chapter discusses the concept of literature in the modern era, defining it as eloquent and influential expression that conveys ideas and emotions through an artistic style. It also examines the origins of modern literature and the factors that contributed to its emergence, such as contact with Western civilization, the translation movement, printing, journalism, and educational missions. In addition, it presents its main forms, including free verse, prose poetry, the novel, the short story, and drama.The second chapter addresses the development of modern Arabic literature, highlighting the main factors that contributed to its flourishing, such as the spread of journalism and printing presses, the establishment of schools and universities, reform movements, and the advancement of translation and linguistic academies. It also discusses the main characteristics of modern literature, including renewal, diversity, interest in social and human issues, intellectual freedom, and interaction with global cultures. Furthermore, it reviews the most important modern literary schools: the Neoclassical school, Romanticism, Realism, and Symbolism, with reference to their prominent figures.The research concludes that modern Arabic literature contributed to the renewal of Arab thought and literature, introduced new literary genres such as the novel and drama, and contributed to the development of literary criticism. Thus, it became an effective means of expressing the issues of society and humanity and a manifestation of cultural revival in the Arab world.
Keywords: Modern Arabic Literature, Literary Revival, Literary Renewal, Modern Literary Schools.